ANALISA PERBANDINGAN PENERAPAN PBR DAN NON PBR PADA PROTOCOL OSPF UNTUK KONEKSI INTERNET - Raisul Azhar (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2015)
The implementation of quota policies to limit the use of the Internet, such as limiting the use of streaming media applications, download and upload activity has a purpose in order to maintain the performance of computer networks, especially companies / organizations that have low Internet bandwidth capacity. Implementation of Policy Based Routing (PBR) means choosing a path or a different route from the routing table to reach the destination address of data packets transmitted. Router device without applying the PBR will choose a path based on the IP address of the destination.This research was conducted by adopting the method NDLC in comparing the routing policy. The stages through which the problem analysis, design and simulation prototype network topology. At this stage of prototype Simulation is done by confguring and testing the Quality of Service (QoS) for network design. Results achieved in the form of comparisons PBR application on the router and use of NON PBR for the implementation of a policy to optimize traffc transmission of data packets or internet traffc usage by users.